Development of Cardiometabolic Health indicators to advance the quality of spinal cord injury rehabilitation: SCI-High Project. (30th September 2019) - Wiest, Matheus J.; West, Christopher; Ditor, David; Furlan, Julio C.; Miyatani, Masae; Farahani, Farnoosh; Alavinia, S. Mohammad; Oh, Paul I.; Bayley, Mark T.; Craven, B. Catharine
Abstract : Context: Spinal cord injury or disease (SCI/D) leads to unchanged low-density lipoprotein and cholesterol, very low high-density lipoprotein a form of dyslipidemia and physical inactivity which combine to increase risk of morbidity and mortality from cardiometabolic disease. Herein, we describe the selection of structure, process and outcome indicators for adults in the first 18 months post-SCI/D rehabilitation admission. Methods: A Pan-Canadian Cardiometabolic Health Working Group was formed to develop a construct definition. Cardiometabolic risk factors were summarized in a Driver diagram. Release of the Paralyzed Veterans of America "Identification and Management of Cardiometabolic Risk after Spinal Cord Injury" and the International Scientific Exercise Guidelines: "Evidence-based scientific exercise guidelines for adults with spinal cord injury", informed the group's focus on prevention strategies to advance this Domain of rehabilitation admission. Results: The structure indicator identifies during rehabilitation the presence of appropriate time and resources for physical exercise prescription. Process indicators are lipid profile assessment at rehabilitation admission and documented exercise prescriptions prior to discharge. The outcome indicators track patient's knowledge retention regarding exercise prescription at discharge, current exercise adherence and lipid status 18 months after rehabilitation discharge. Conclusion: Routine national implementation of these indicators at the specified time points will enhance efforts to detect dyslipidemia and assure routine participation in endurance exercise. These indicators align with international initiatives to improve cardiometabolic health through interventions targeting modifiable risk factors specifically endurance exercising and optimal lipid profiles, crucial to augmenting cardiometabolic health after SCI/D.